REVIEW OF INFRASTRUCTURE AND LOCAL PORT SERVICES (LPS) AT MERAK AND BAKAUHENI CROSSING PORTS - Hatina, Damaida; Surnata, Surnata; Triwahyuni, Siti Nurlaili; Widjatmoko, Eko Nugroho; Djulfi, Isman; Kristia, Aurellia Okta (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
The Merak and Bakauheni Crossing Ports are a port connection for the Merak-Bakauheni crossing which is referred to as the main bridge in connecting the islands of Java and Sumatra. Each port has various facilities that can support port operational activities, one of which is Local Port Services (LPS). Local Port Services (LPS) is a service for ship traffic that is only limited to providing information about port and terminal needs and operational data that is not responsive to shipping traffic within the coverage area of the relevant station. The feasibility of these facilities is very important for the purpose of communication with ships that will enter and exit the pier as well as supervision of the arrival and departure process of ships. The method used is an observation method so that data is obtained by making observations directly at the research location. At the Merak and Bakauheni crossing ports, there are already Local Port Services (LPS) facilities but based on the results of observations in the field, there are discrepancies with applicable regulations such as the condition of room needs and the competence of human resources needed for Local Port Services (LPS) activities. This study uses the Gap Analysis method to determine the gap between existing conditions and the Regulation of the Director General of Land Transportation Number: PR-DRJD 4 of 2021. Based on the results of the research by looking at the situation firsthand, it was found that there was a discrepancy with the Regulation of the Director General of Land Transportation Number: PR-DRJD 4 of 2021, namely trees and gangways that obstruct the indicators of free view to the water coverage area and the required human resource competencies have not been fulfilled. Efforts are made so that Local Port Services (LPS) activities can run optimally by felling trees and planning the relocation of Local Port Services (LPS) activities and involving existing human resources in various education and training activities in accordance with the required competencies.